PocketQube development for earth exploration and vegetation monitoring - Dhakal, Rabin; Ghimire, Abhishek; Nepal, Sanjay; Khanal, Kapalik (Journal of Innovations in Engineering Education, 2022)
A PocketQube is being popular these days due to the enhancement in technologies for space research and earth observation. It is extremely vital to analyze the condition of vegetation on the earth surface because deforestation, forest fire and smuggling of precious plants have been increasing dramatically. The camera module in the payload captures the image from the space which helps in analyzing the vegetative condition of the forest on the earth’s surface. The provided image data is huge in order to maintain the quality of the images it captures. Hence, the received image data is further divided into chunks. Each chunks holds 64bits of hex values of each pixels of the image. The subsequent real time Image data is transmitted to the ground station and the received image is checked, analyzed and displayed on the screen. The received data is regenerated by combining the received chunks at a time at ground station. Based on the provided images further image processing activities are conducted in order to understand the condition of vegetation by calculating the vegetative index of each pixels in the received images.